IL-1Ra (recombinant human IL-1 receptor antagonist) in the treatment of rheumatoid arthritis: the efficacy - L. Cozzi; M. Vezzù; U. Fiocco; S. Todesco (PAGEPress Publications, 2011)
Interleukin 1 receptor antagonist (IL-1Ra) is a naturally occurring IL-1 inhibitor, acting as a "receptor antagonist", which blocks IL-1 mediated signal transduction. In 1990 IL-1Ra was cloned and later on, a large numbers of studies led to disclosure of the crucial importance of the imbalance between IL-1 and IL-1Ra in the pathogenesis of rheumatoid arthritis (RA). In 1991, almost 8 years after the initial isolation of IL-1, recombinant IL-1Ra (IL-1ra, Kineret) was introduced in clinical trials involving patients with RA. Between 2001 and 2002 IL-1ra was approved by the US Food and Drug Administration and by the European Agency for the Evaluation of the Medicinal Products and in 2003 it was registered in Italy, too. In RA recombinant IL-1ra has been evaluated in 5 randomized, placebo-controlled clinical trials involving more than 2900 patients. Two of the trials involved the use of IL-1ra as monotherapy versus placebo and two trials in combination with methotrexate (MTX); the last trial explored the use of a fixed 100 mg/day IL-1ra dosage in a RA patient population including a wide array of co-morbid conditions as well as concomitant medications. The studies confirmed both the efficacy and the safety of IL-1ra in patients with active and severe RA. 43% of patients receiving 150 mg/day IL-1ra achieved a 20% response according to the American College of Rheumatology criteria (ACR20), compared to 27% in the placebo group. In the MTX combination therapy study, 42% of the patients receiving 1 mg/Kg/day of IL-1ra achieved an ACR20, 24% an ACR50 and 10% an ACR70. In each study, significant improvements in the Health Assessment Questionnaire scores (HAQ) were observed. There were rapid gains in the number of days at work or domestic activity in the treated patients, and the increases in productivity were dose related. At early 24 weeks, there was significant reduction of both the score for progression of joint space narrowing (JSN) and the Total modified Sharp-Genant score (a combination of erosion and JSN) in all treatment groups (30,75 and 150mg/day). The clinical benefits of treatment with daily subcutaneous injections of IL-1ra in active RA patients were maintained for up to 48 weeks. IL-1ra, a selective inhibitor of the IL-1 pathway, represents an important new biologic approach to treating patients with RA, that significantly reduces clinical signs and symptoms of the disease and joint destruction and has proved safe and well tolerated also in combination with other DMARDs and concomitant medications.